Observational Study of the Relationship Between the Level of Lead and Hemoglobin in Women from Mining Centers in Huancavelica - Peru at More Than 3900 Mas L May, 2022 - Cardenas-Pineda, L.; Quispe, E.T.; Condori, S.J.; Guerra-Olivare, T.; Lopez, A.L.; Cieza-Terrones, M.C.; Delgado, A.; Alva-Mantari, A.A. (Seventh Sense Research Group, 2023)
The objective of this study was to determine the relationship between the level of lead in blood and the level of hemoglobin in women of childbearing age who live under the influence of mining centers in the Huancavelica region during the year 2022. Methodology: observational, prospective, cross-sectional, relational level research, in 132 women, with a minimum of three months of residence in Huachocolpa, Mimosa and Cochaccasa. Statistical analysis was done with Kendall's Tau b. Results: The majority were single (52.27%), young (60.61%), with a normal nutritional status (65.15%); 36.36%, the most frequent age (60.61%) was between 19 to 34 years, the average age was 28 years old, weight 55.65 kg and height 153 cm and 75% live in the area, more than 5 years old. Most of the houses were made of rustic material (82.56% adobe wall, 64.5% calamine or Eternit roof), 81% had basic sanitation and were located 1 km from the tailings, 75% of the families they had 3 or more members, 42.42% have children under 5 years old and 55.3% from 5 to 12 years old. None practice preventive measures and 94.70% want the information to avoid contamination by heavy metals. The lead level was 0.50 – 7.20 Ug/dL, the mean was 1.35 ± 1.11, and the Hb was 7.80 – 21.60 g/dL, and the mean was 11.85%, 3 out of 5 women had anemia; there a moderate negative relationship with a p-value from 0.000 to 99% confidence. Conclusions: low lead levels also affect hematopoiesis at higher blood lead levels and lower Hb levels.
Keywords: Observational study; Hemoglobin; Medicine; Environmental science; Internal medicine; https://purl.org/pe-repo/ocde/ford#3.02.27